Development of a rapid antigen-based lateral flow assay for tick-borne spotted fever rickettsioses. - Richard Willson; Yingxin Zhao; Kristen Brosamer; Yogita Pal; Lucas S Blanton; Esteban Arroyave; Carsen Roach; David H Walker; Katerina Kourentzi; Rong Fang (PLoS ONE)
Tick-borne spotted fever rickettsioses (SFRs) continue to cause severe illness and death in otherwise-healthy individuals due to lack of a timely and reliable diagnostic laboratory test. We recently identified a diagnostic biomarker for SFRs, the putative N-acetylmuramoyl-l-alanine amidase RC0497. Here, we developed a prototype laboratory test that targets RC0497 for diagnosis of SFRs. The concentrations of RC0497 in sera of Rickettsia rickettsii-infected guinea pigs and R. conorii-infected mice were determined by stable isotope dilution-parallel reaction monitoring mass spectrometry (SID-PRM-MS), ranging from 0.1 to 1.1 ng/ml. Using europium chelate nanoparticle reporters, we developed a lateral flow assay (LFA) and evaluated the test with a panel of serum samples of mock and experimentally infected animals. Interestingly, 21 of 22 (95.5%) serum samples from R. rickettsii-infected guinea pigs and R. conorii-infected mice yielded positive results with a ratio of test line / control line greater than the cutoff value determined for non-infected animals. All uninfected samples were in agreement with the intended results, suggesting that the initially assessed specificity of the test is 100%, among these samples. Mice infected with a lethal dose of R. conorii and treated with doxycycline on day 3 post-infection (p.i.), upon RC0497 detection by LFA, displayed significantly decreased rickettsial loads, comparable to the sublethal infection group on day 5 p.i.. A panel of human serum samples spiked with various concentrations of recombinant RC0497 were analyzed by LFA, suggesting that the limit of detection of the LFA was 0.64 ng/mL. These findings suggest that the timely detection of RC0497 by a europium LFA offers guidance for treatment, leading to a significant improvement in infection outcomes. This work, for the first time, shows significant promise for a rapid and easy-to-use platform offering a timely diagnostic assay for severe SFRs.